PENGARUH BAHAN BAKU IKAN TERHADAP NILAI ORGANOLEPTIK DAN NILAI KANDUNGAN GIZI PRODUK STIK IKAN DI KABUPATEN KOTAWARINGIN BARAT - Vita Yanuar; Manis Suharjo; Abjudelmen Igas (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2016)
The fisheries sector has a potential force in supporting development in the region, particularly the nutritional needs of local communities in addition to being a factor of regional economic growth. Diversification of products processed fishery products into one solution for success in nutrition. Stick fish into processed products to diversify the selection of raw material use fish that generally only use mackerel fish. The research objective was to determine the organoleptic properties of the product stick fish on the fish raw material and determine the effect of different types of fish as the raw material to the nutritional value of the product of fish sticks. The experimental design used in this study is completely randomized design (CRD) single factor consisting of 3 treatments 3 repetitions. Treatment use of raw materials of different fish include mackerel, manyung and remang. The results showed that the organoleptic stick mackerel have the highest average total of 8.38 (so ideal) compared with other fish sticks. The use of raw materials of different fish to produce value or nutrient content is not much different. That is very possible manyung and remang fish as the choice of raw materials substitute mackerel fish.